2018
DOI: 10.1039/c8sc01956h
|View full text |Cite
|
Sign up to set email alerts
|

Identifying site-dependent reactivity in oxidation reactions on single Pt particles

Abstract: IR nanospectroscopy measurements revealed the influence of oxidizing reaction conditions on the reactivity of different surface sites on Pt particles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
52
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 54 publications
2
52
0
1
Order By: Relevance
“…The strong NHC-metal interaction enabled the formation of stable self-assembled monolayers (SAMs) of NHCs on metals [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] , metal-oxides 22,23 and semimetals 24 . The wide chemical-tunability of NHCs led to utilization of NHC-based SAMs as biosensors 10,25,26 , molecular probes for surface reactivity [27][28][29] , and co-catalysts 3,[30][31][32][33] .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The strong NHC-metal interaction enabled the formation of stable self-assembled monolayers (SAMs) of NHCs on metals [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] , metal-oxides 22,23 and semimetals 24 . The wide chemical-tunability of NHCs led to utilization of NHC-based SAMs as biosensors 10,25,26 , molecular probes for surface reactivity [27][28][29] , and co-catalysts 3,[30][31][32][33] .…”
mentioning
confidence: 99%
“…For example, aromatic organic layers were formed on conductive or semiconductive surfaces following electrochemical reduction of aryl diazonium salts 39,40 . However, utilization of the electrochemical deposition approach toward surface anchoring of NHCs was not previously demonstrated, Herein, 1,3-bis(2,4-dinitrophenyl)-imidazole (NO 2 -NHC) 16,17,27 was used as a model system for addressable carbenes and was ECdeposited on various metal surfaces. Quantitative analysis revealed that EC deposition induced monolayer formation of NO 2 -NHCs on Au films with higher surface density and improved chemical stability than those prepared by base-induced deprotonation.…”
mentioning
confidence: 99%
“…[1][2][3] The strong NHC-metal interaction enabled the formation of stable and chemically-addressable self-assembled monolayers (SAMs) of NHCs on metals, [4][5][6][7][8][9][10][11][12][13][14][15][16] metal-oxides 17,18 and semimetals. 19 The wide chemical-tunability of NHCs led to utilization of NHC-based SAMs as biosensors, [20][21][22] molecular probes for surface reactivity [23][24][25] and co-catalysts. 2,[26][27][28][29] NHC-based SAMs have been prepared thus far by two deposition techniques; namely liquid-and vapor-phase deposition (Scheme 1a and 1b, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…In this work, nitro-functionalized NHCs (NO 2 -NHCs) 10, 11,23 were utilized as a model system for addressable carbenes and were EC-deposited on Au surfaces. The ECdeposition leads to high spatial and temporal proximity between the deprotonation and surface-anchoring of NHCs, while sustaining a small and constant concentration of active carbenes in the solution.…”
Section: Introductionmentioning
confidence: 99%
“…Destaca-se que, embora o potencial de SINS já esteja sendo demonstrado em diversos campos do conhecimento, 9,[27][28][29][30] tal técnica ainda não está sendo usada de forma sistemática na investigação de bens culturais, ao contrário de µ-FTIR com radiação sincrotron. 31,32 Atualmente, além do Laboratório Nacional de Luz Síncrotron (LNLS), apenas 2 laboratórios no mundo realizam o experimento SINS de forma aberta à comunidade.…”
Section: Introductionunclassified